THE RIGHT TO EDUCATION AS A FUNDAMENTAL REPUBLICAN PUBLIC POLICY FOR THE DEVELOPMENT OF CITIZEN DEMOCRACY (Interdisciplinary Studies Journal, 2024)
The article's theme is the link between the republican form of government and the right to education as inseparable historical, political and philosophical concepts. The general objective seeks to analyze the trajectory of the tradition of modern republicanism with the development of republican public education/instruction. Since the genesis of the ideas of public instruction and republican education have their origins in the revolutionary events of the 18th century. In this context, the following question arises: Has public education, in a secular form, liberating political opinion and belief in reason, become a fundamental right for the development of citizen participation in political matters of common interest? Faced with this question, the technique used for qualitative research was bibliographic with deductive logic and an analytical-hermeneutic approach. It is concluded that eighteenthist thinking and ideas enabled the right to education to mature, enabling great advances in the modern world and which consolidated it as one of the significant conditions for access to understanding rights and duties and strengthening the dignity of the human person.
Keywords: Education; Republic; Democracy; Fundamental Rights